2020
DOI: 10.1161/jaha.119.015154
|View full text |Cite|
|
Sign up to set email alerts
|

Metformin Improves Cardiac Metabolism and Function, and Prevents Left Ventricular Hypertrophy in Spontaneously Hypertensive Rats

Abstract: Background In spontaneously hypertensive rats ( SHR ) we observed profound myocardial metabolic changes during early hypertension before development of cardiac dysfunction and left ventricular hypertrophy. In this study, we evaluated whether metformin improved myocardial metabolic abnormalities and simultaneously prevented contractile dysfunction and left ventricular hypertrophy in SHR . Methods and Results SHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…While it remains to be determined as to how these early metabolic changes give rise to LVH, the activation of mTOR has been proposed as a contributing factor. Similarly, profound myocardial metabolic changes have been found to occur prior to the progression of LVH and cardiac dysfunction in spontaneously hypertensive rats [38].…”
Section: Metabolic Disturbancesmentioning
confidence: 92%
“…While it remains to be determined as to how these early metabolic changes give rise to LVH, the activation of mTOR has been proposed as a contributing factor. Similarly, profound myocardial metabolic changes have been found to occur prior to the progression of LVH and cardiac dysfunction in spontaneously hypertensive rats [38].…”
Section: Metabolic Disturbancesmentioning
confidence: 92%
“…There are many literatures that activation of pro-survival kinases, such as ERK and AMPK, can achieve strong cardiac protection in myocardial reperfusion 4,20,31 . Activation of myocardial AMPK has been shown to display salutary effects on ischemic heart disease and glucose homeostasis [32][33][34][35][36] , we, therefore, hypothesized that the AMPK signaling pathway is primarily involved in the protective effects of IF1 as an underlying mechanism. At the cellular level, AMPK activation was found to result from ROS production induced by IF1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that metformin significantly suppressed the development of Ang II-induced cardiomyocyte hypertrophy as evidenced by reductions in cardiomyocyte surface area, reduced expression of hypertrophy-associated genes ANP and BNP in Ang II-stimulated cardiomyocytes. Metformin has also been demonstrated to serve cardioprotective effects by reducing left ventricular hypertrophy in patients with coronary artery disease, insulin resistance and pre-diabetes (27,28) Additionally, previous studies have demonstrated that metformin can inhibit protein synthesis by activating MAPK, functioning in the anti-hypertrophic pathway in cardiomyocytes (29,30).…”
Section: Discussionmentioning
confidence: 99%